Gambaran profil lipid dan dislipidemia pada remaja dengan obesitas di kota Denpasar, Bali, Indonesia - Luh Gede Yuliadewi NS; I Made Arimbawa (DiscoverSys Inc., 2020)
Background: Obesity results in an increase fat accumulation in the body, related to blood lipid levels, and causes dyslipidemia. Dyslipidemia is one of the main risk factors for cardiovascular events. This study aims to determine the overview of lipid profiles and dyslipidemia in adolescents with obesity in the city of Denpasar, Bali, Indonesia.Method: A descriptive observational analytic study with a cross-sectional design was conducted on 51 obese adolescents in Denpasar using a two-stage random sampling technique. The variables assessed included examining lipid profiles such as total cholesterol, High-Density Lipoprotein (HDL), Low-Density Lipoprotein (LDL), and triglycerides. Data were analyzed with SPSS version 23 for Windows.Results: The results showed that there were 25 male subjects (49.01%) and 26 female subjects (50.99%) with an average age of 15.00±3.41 years. The mean body weight was 89.39±9.81 kg, the mean height was 158.62±7.31 cm, and the Body Mass Index (BMI) was 33.56±3.36 kg/m2. The mean total cholesterol 170.57 ± 25.92 mg/dl, HDL 47.59 ± 10.24 mg/dl, LDL 113.61 ± 26.64 mg/dl, and triglycerides 126.14 (75.00) mg/dl. Dyslipidemia status based on criteria for total cholesterol levels was found in 27 subjects (52.9%), followed by HDL (23.59%), LDL (52.90%), and based on triglyceride levels of 15.70% subjects. Dyslipidemia based on the overall lipid profile was found in 36 subjects (70.60%).Conclusions: Most subjects had total cholesterol levels above normal, HDL levels below normal, LDL levels above normal, and most subjects experienced dyslipidemia. Latar belakang: Obesitas mengakibatkan peningkatan akumulasi lemak berlebihan dalam tubuh, berkaitan dengan kadar lipid darah dan menyebabkan terjadinya dislipidemia. Dislipidemia merupakan salah satu faktor resiko utama untuk terjadinya kardiovaskular. Penelitian ini bertujuan untuk mengetahui gambaran gambaran profil lipid dan dislipidemia pada remaja dengan obesitas di kota Denpasar, Bali, Indonesia.Metode: Penelitian observasioanal deskriptif dengan desain potong lintang dilakukan terhadap 51 remaja dengan obesitas di kota Denpasar menggunakan teknik two-stages random sampling. Variabel yang dinilai meliputi pemeriksan profil lipid seperti kolesterol total, High Density Lipoprotein (HDL), Low Density Lipoprotein (LDL), dan trigliserida. Data dianalisis dengan SPSS versi 23 untuk Windows.Hasil: Hasil penelitian menunjukkan bahwa terdapat 25 subyek berjenis kelamin laki-laki (49,01%) dan 26 subyek perempuan (50,99%) dengan rerata usia 15,00±3,41 tahun. Rerata berat badan 89,39±9,81 kg, rerata tinggi badan 158,62±7,31 cm dan Indeks Massa Tubuh (IMT) 33,56±3,36 kg/m2. Rerata kolesterol total 170,57±25,92 mg/dl, HDL 47,59±10,24 mg/dl, LDL 113,61±26,64 mg/dl, dan trigliserida 126,14 (75,00) mg/dl. Status dislipidemia berdasarkan kriteria kadar kolesterol total didapatkan pada 27 subyek (52,9%), diikuti dengan HDL (23,59%), LDL (52,9%), dan berdasarkan kadar trigliserida sebesar 15,70% subyek. Dislipidemia berdasarkan keseluruhan profil lipid didapatkan pada 36 subyek (70,6%).Simpulan: Sebagian besar subyek memiliki kadar kolesterol total diatas normal, kadar HDL di bawah normal, kadar LDL di atas normal, dan sebagian besar subyek mengalami dislipidemia.